Influence of helium ions beams with energies 0.12 MeV on sputtering process on surface of tungsten - Manuilenko, O.V.; Prokhorenko, E.M.; Pavlii, K.V.; Zajtsev, B.V.; Dubniuk, S.N.; Lytvynenko, V.V.; Kasatkin, Yu.A.; Prokhorenko, T.G. (Problems of Atomic Science and Technology, 2023)
The samples of tungsten with a purity of 99.5 and 99.7% were irradiated with helium ion beams (EHe⁺ = 0.12 MeV). The total sputtering coefficients for the sample depth up to 60 Å from the surface of sample were obtained. It was found that on the surface of tungsten, the number of pits (the flecking effect) significantly exceeds the number of bubbles (the blistering effect). The damage profiles of the surface of tungsten as a result of irradiation with helium ions are calculated. The areas of maximal display of effects of damage are determined. Проведено опромінення зразків вольфраму з чистотою 99,5 і 99,7% пучками іонів гелію (EHe⁺ = 0,12 МeВ). Отримано сумарні коефіцієнти розпилення за глибиною зразка до 60 Å від поверхні зразка. Знайдено, що на поверхні зразків вольфраму кількість ямок (ефект флекінгу) істотно перевищує кількість бульбашок (ефект блістерингу). Пораховані профілі пошкодження поверхні вольфраму в результаті опромінення іонами гелію. Визначено зони максимального прояву руйнівних ефектів.